2009
DOI: 10.1007/s11010-009-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

The Nm23-H1–h-Prune complex in cellular physiology: a ‘tip of the iceberg’ protein network perspective

Abstract: Nm23-H1 (also known as NDPKA) and h-Prune form a protein complex that is part of a little-understood protein network. Modifications of this complex correlate with cancer status. Here, we focus on the role of the Nm23-H1-h-Prune complex in cellular physiology, through an analysis of the balance between the 'bound' and 'non-bound' states of Nm23-H1 and h-Prune, whereby we speculate on the 'read-out' during cell homeostasis under non-balanced conditions. We have analysed the biochemical activities of both Nm23-H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…S9A). BCH inhibits RhoA, a small GTPase that regulates the cytoskeleton, cell adhesion, and migration (16), whereas DHHA2 interacts with Nm23-H1, a metastasis suppressor (17). We found that endogenous PRUNE2 coimmunoprecipitates with RhoA and Nm23-H1 (Fig.…”
Section: Pca3mentioning
confidence: 63%
See 1 more Smart Citation
“…S9A). BCH inhibits RhoA, a small GTPase that regulates the cytoskeleton, cell adhesion, and migration (16), whereas DHHA2 interacts with Nm23-H1, a metastasis suppressor (17). We found that endogenous PRUNE2 coimmunoprecipitates with RhoA and Nm23-H1 (Fig.…”
Section: Pca3mentioning
confidence: 63%
“…S10 E-J). These results, along with the established functions of interacting proteins (16)(17)(18), suggest that PRUNE2 primarily decreases tumor growth by inhibiting cell proliferation but also affects adhesion, spreading, and migration. We subsequently extended these results to human tumor xenograft models; LNCaP prostate cancer cells stably expressing PRUNE2-shRNA, ectopic PCA3, PCA3-shRNA, or controls were s.c. administered into SCID mice.…”
Section: Pca3mentioning
confidence: 80%
“…13 Other functions identified for polyP in mammalian cells include cell proliferation, 14 angiogenesis, 15 apoptosis, 16 osteoblast function, 17 bone mineralization, 18,19 energy metabolism, 20 and tumor metastasis. 21,22 In this review, we explore the recently reported roles of polyP in blood clotting and inflammation. Studies from our laboratory and others have shown that polyP acts at the beginning, middle, and end of the blood clotting cascade (Figure 2), with prohemostatic, prothrombotic, and proinflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 H-prune contains two DHH domains at its N-terminus, followed by a third C-terminal domain, which was previously shown to be responsible for the interaction with different partners such as GSK-3beta and with Nm23-H1. 27,28 The conformational analysis of the C-terminal domain of h-prune performed by nuclear magnetic resonance showed that it assumes a random coil conformation with the exception of some protein regions with helical structural propensity and a disulfide bridge as unique rigid linkage. 20 In particular, the recombinant C-terminal domain of h-prune (residues 354-453, c-prune) was sufficient to bind the characterized interacting Nm23-H1 endogenous protein as verified by Western blotting analysis and nuclear magnetic resonance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%